Haplotype variation of Green Revolution gene Rht‐D1 during wheat domestication and improvement. Issue 8 (11th June 2014) - Zhang, Chihong; Gao, Lifeng; Sun, Jiaqiang; Jia, Jizeng; Ren, Zhenglong
Abstract Green Revolution made a substantial contribution to wheat yields worldwide in the 1960s and 1970s. It is of great importance to analyze the haplotype variation of Rht‐D1, the Green Revolution gene, during wheat (Triticum aestivum L.) domestication and breeding to understand its evolution and function in wheat breeding history. In this study, the Rht‐D1 and its flanking regions were sequenced and single nucleotide polymorphisms were detected based on a panel of 45 accessions of Aegilops tauschii, 51 accessions of landraces and 80 accessions of commercial varieties. Genetic diversity in the wild accessions was much higher than that in the varieties and higher than that reported previously. Seven haplotypes (Hapl I to Hapl VII) of Rht‐D1 were identified and their evolutionary relationships were proposed. In addition to the well‐known Green Revolution allele Rht‐D1b, Hapl VII (an allele Rht‐D1k) was identified in early breeding varieties, which reduced plant height by 16%. The results suggested that Rht‐D1k had been used in breeding before the Green Revolution and made a great contribution to wheat production worldwide. Based on the breeding history and molecular evidence, we proposed that the wheat Green Revolution in China and International Maize and Wheat Improvement Center (CIMMYT) occurred independently.